Experimental study of ice slurry production system using direct contact heat transfer of RC318 and water in a horizontal pipe. (February 2019) - Zhang, Yaokang; Su, Lin; Dong, Kaijun; Liu, Tengqing
Abstract: With the direct contact ice production technique, ice blockage around the injector, large refrigerant charge and difficulty in separating the refrigerant from water always occur. In order to overcome these problems, the combined of a spiral jet (SPJT) and a horizontal PVC pipe is developed to achieve continuous ice production, and RC318 is selected as the refrigerant. The effect of rotational speed of the compressor on water temperature decrement, ice production rate, ice packing factor (IPF), COP and coefficient of ice producing performance (CIPP) is investigated in this study. The results show that as the rotational speed increases, a faster drop of water temperature and a higher ice production rate are obtained, which result in higher IPF under fixed duration. However, an increase in rotational speed leads to a decrease in COP. The maximum CIPP is 6.64×10 -3 kg/kJ at rotational speed of 2700rpm. Moreover, at high rotational speed of 2820rpm, the cooling capacity becomes worse at the later stage of ice production process. Conclusively, the rotational speed of 2700rpm is considered as the optimal working condition.